Bartók and the Topic of Drunkenness. Theory in Performance - Hellaby, Julian (Res Facta Nova, 2025)
This article considers Mikhail Bakhtin’s notion of carnivalisation (1984 [1968]), which he divides into four categories, the second of which is eccentric or inappropriate behaviour where conventionally unacceptable behaviour becomes normalised in a carnival setting. Bakhtin believed that real-life carnivalisation, as practised in ancient and medieval societies, had gradually become eclipsed by its transfer to literature, and this essay further transfers it to music. Burlesque may be regarded as a particular manifestation of the Bakhtinian carnival and the focus of this article, the second of Bartók’s Three Burlesques Op. 8/c (“A Little Tipsy”), features what is here regarded as the topic of drunkenness. The carnivalisation of drunken behaviour is very much apparent in this music because outside the context of the carnival, drunkenness is generally the object of official censure whereas within the carnival context, as processed through Bartók’s music, it is rendered harmless, humorous and socially acceptable to the attentive listener. The notion of drunkenness as a topic is defended and this is followed by an examination of how best to portray it in performance – how to project the topic but without so much musical distortion that the piece’s coherence collapses. There are three principal sources for the performer to consult: the piano score (1911), the orchestral score of the composer’s later transcription (1931) and Bartók’s own recorded performance (1929). The author negotiates between these three sources, assessing a variety of performances both orchestral and pianistic, offering a personal interpretative strategy in the process.